THE IN VITRO AND IN VIVO EFFECTS OF Persea Americana ETHANOL EXTRACT AS AN ANTIHYPERTENSIVE AND ANTIOXIDANT IN PREDNISONE-INDUCED RATS - Elisa, Novi; Dian Advistasari, Yustisia; Sari, Wulan Kartika; Pratiwi, Mustika Endah; Tobi, Claudius Hendraman Boli; Murti, Bayu Tri; Putri, Athika Darumas (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
Hypertension impacts the quantity of free radicals within the body. This study aimed to investigate the effect of antihypertension based on free radical levels in the predni-sone-induced rats, focusing on evaluating specific anti-hypertensive fraction of avoca-do leaves. The study's methods conducting GC-MS, anti-hypertensive, and assessing malondialdehyde levels and catalase enzyme. Systolic blood pressure measurements indicated that the positive control (131 ± 3 mmHg) and ethyl acetate fraction (136 ± 4 mmHg) were statistically similar, significantly different from the negative control group. Diastolic blood pressure measurements showed a blood pressure decreasing in posi-tive control (105 ± 7) that similar statistically with ethyl acetate fraction (104 ± 6), and significantly difference with negative control group. Malondialdehyde levels were nota-bly elevated in both the positive control (37.79 ± 5.47) and ethyl acetate fraction (38.01 ± 5.47) compared to the negative control (-9.07 ± 10.10), indicating increased free rad-ical. Catalase activity demonstrated significant differences, with the positive control (44.06 ± 5.44) and ethyl acetate fraction (44.05 ± 5.45) showing similar levels, both substantially higher than the negative control (13.90 ± 21.50). In summary, this study indentificates several flavonoid compounds that promising anti-hypertension effect from ethyl acetate fraction of avocado leaves extract.